Public perceptions of the societal impact of elite sport: Scale development and testing - De Rycke, J.; De Bosscher, V.; Funahashi, H.; Sotiriadou, P. (Journal of Sport Management, 2019)
Many Nations are increasingly investing public money in elite sport on the belief that this will trigger a range of benefits for the population. However, there is lack of insight into how the population perceives elite sport`s impact on society. This study developed and tested a measurement scale assessing the publics` beliefs of the positive and negative societal impacts that could potentially flow from elite sport. A sample of the Belgian population (N = 1,102) was surveyed. A 32-item scale was built using principal component and confirmatory factor analysis procedures for which the goodness-of-fit indices were excellent. Multivariate analysis revealed that the Belgian population perceived elite sport to have mostly positive societal impacts. The study findings can serve researchers wanting to measure the perceived potential positive and negative societal impacts of elite sport.